2023
DOI: 10.3390/microorganisms11010124
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus and MRSA in Livestock: Antimicrobial Resistance and Genetic Lineages

Abstract: Animal production is associated with the frequent use of antimicrobial agents for growth promotion and for the prevention, treatment, and control of animal diseases, thus maintaining animal health and productivity. Staphylococcus aureus, in particular methicillin-resistant S. aureus (MRSA), can cause a variety of infections from superficial skin and soft tissue infections to life-threatening septicaemia. S. aureus represents a serious public health problem in hospital and community settings, as well as an econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 102 publications
0
24
1
2
Order By: Relevance
“…Of these, 13 belonged to spa type t359, one to spa type t2770 and one was non-typable. This clone is usually associated with livestock and rarely with human infections [ 36 , 37 ]. Spa type t359 was previously confirmed in Slovenia among suspected human CA-MRSA isolates in 2014 and 2015 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 13 belonged to spa type t359, one to spa type t2770 and one was non-typable. This clone is usually associated with livestock and rarely with human infections [ 36 , 37 ]. Spa type t359 was previously confirmed in Slovenia among suspected human CA-MRSA isolates in 2014 and 2015 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, attention should be on the effect of weather conditions with high temperature, humidity, and particulate matter concentration on Staphylococcus [47][48][49] . Infection with Staphylococcus may cause acute or chronic infectious diseases in poultry, with common clinical manifestations of skin blisters and abscesses [50][51][52] . Furthermore, we found that temperature affects the concentration of bioaerosols.…”
Section: Discussionmentioning
confidence: 99%
“…MRSA has been recognized in hospitals, community and livestock animals and the epidemiology of MRSA is undergoing a major evolution among humans and animals in the last decade ( Chen et al, 2021 ; Yu et al, 2021 ). Since the livestock-associated MRSA (LA-MRSA) was first recognized in Europe in 2003, LA-MRSA has been identified in numerous countries around the world, including China ( Cui et al, 2009 ; Silva et al, 2023 ). Multilocus sequence typing (MLST) analyzes seven constitutively expressed (housekeeping) genes that are essential to cellular functioning of organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Multilocus sequence typing (MLST) analyzes seven constitutively expressed (housekeeping) genes that are essential to cellular functioning of organisms. LA-MRSA of sequence type (ST) 398 dominates in Europe, Australia and the United States, while LA-MRSA-ST9 is the main epidemic lineage in Asia ( Yu et al, 2021 ; Silva et al, 2023 ). Several studies have identified specific LA-MRSA within the community acquired-MRSA category ( Bisdorff et al, 2012 ; Mascaro et al, 2018 ; Sun et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%